Influence of Antimony Micro-Alloy Addition on the Mechanical Properties of Carbidic Austempered Ductile Iron (CADI) - Aliu, A.; Barnabas, A. A.; Rufai, A. M.; Okpo, S. O. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2022)
In this research work, the influence of antimony micro-alloy addition on the hardness property, impact energy and wear resistance of carbidic austempered ductile iron (CADI) was investigated. Rod-shaped samples were produced using a sand casting technique to investigate the influence of antimony micro-quantities on the microstructural modification of the high manganese content (CADI). Selected mechanical properties of the product (CADI) have been tested.  Rod-shaped samples were produced using a sand casting technique to investigate the influence of antimony micro-quantities on the microstructural modification of the high manganese content (CADI). Selected mechanical properties of the product (CADI) have been tested. Rod-like shape samples were produced by sand casting technique used for evaluating the influence of micro - quantities of antimony on the microstructural modification of high manganese content carbidic austempered ductile iron (CADI) with respect to the selected me 7chanical properties. Six compositions of carbidic ductile iron (CDI) with varying antimony content ranging from 0.096 % to 0.480 wt. % were produced, having equivalent carbon of hyper-eutectic composition (4.43). These samples were heated to austenitic temperature of 910ºC and subjected to austempering temperature, 300ºC for period of 1-3 hours. Microstructural examination of the samples was carried out to study the matrix and reinforcing phases present. The abrasion wear resistance was evaluated in accordance with the ASTM G 65 standard. The results show that; the obtained wear resistance values ranging from 2.35E8 to 3.29 E9 with respect to unmodified CADI (taken as reference material) The results show that the wear resistance values ranging from 2.35E8 and 3.29 E9 with respect to CADI sample without antimony addition taken as reference material, Rockwell hardness values obtained ranging from 28.6 – 55 HRc and impact toughness values ranges from 46.5 – 53 J for the developed CADI. Micrographs obtain revealed that chunky graphite, blocky carbides and pearlite phases were seen in the as-cast sample without antimony addition while the samples with varying addition of antimony element showed spiky graphite, granular carbide and more pearlite phases. However, after subjecting the samples to austempering processes, the pearlite phase transformed to ausferritic structure, while the carbide and graphite structure remained unaltered. The produced CADI is found to be useful for agricultural implements production.